Assessment of microecology of the oral cavity during the period of adaptation to dual-layer structures of dentures with a obturating part - Yanishen, I.; Fedotova, Olena; Pogorila, A.; Sokhan, M.; Yanishena, Y. (Міністерство охорони здоров'я України, Українська медична стоматологічна академія, 2019)
The purpose of the study . was to study the dynamics of the peculiarities of the representatives of the microbiota of the oral mucosal membrane during orthopedic rehabilitation of patients with removable structures with a obturating part with two-layer bases
Keywords: orthopedic dentistry; two-layer bases; adaptation; obturating part